« Quand on me battait debout, je saignais en pile. » - Gilles Delâtre (Études Caribéennes)
In Guadeloupe, in December 1841, Eugène Vaultier de Moyencourt, owner in the commune of Petit-Canal, was tried by the Assize Court of Basse-Terre for ‘excessive punishment and inhuman treatment of his slaves’. From January to March 1842, Louis-Joseph Vallentin, owner of Joinville in Marie-Galante was tried by the Assize Court of Pointe-à-Pitre for having, in the course of 1838, killed the slave Sébastien. As the abolitionist discourse gained traction in metropolitan France and colonial justice – as said by the public prosecutor – was more lenient, the ‘owners’ of Guadeloupe did not intend to abdicate, arguing in turn the inviolability of private property, racial characteristics of black people that would be unfit for freedom, national interest, and conceptions from religion or classical antiquity that slavery is necessary for the civilization. Between 1840 and 1848, we can identify 21 cases where the arbitrary violence of the master, going as far as cruelty, even sadism, often leads to the death of slaves (Josette Fallope, 1992). This is the case of the Vaultier de Moyencourt and Vallentin cases, which reveal the daily abuse, punishment and torture endured by slaves deemed poisoners. If they end unsurprisingly with the acquittals of the masters, representatives of a plantocracy based on white endogamy and determined to retain power in the colony, they quietly raise a pusillanimous questioning of the impunity of the master by the public prosecutor. Moreover, they let us hear the voices of the slaves who testify. While some remain under the influence, others accuse and describe the torment and crimes. These testimonies, pronounced in Creole, have come down to us translated into French through the clerks (with, however, some words maintained in Creole) in the communication that The Official Gazette of Guadeloupe gave of these trials.